Crude oil fouling : deposit characterization, measurements, and modeling - Coletti, Francesco; Hewitt, G. F. (Geoffrey Frederick) (Amsterdam ; Boston : Gulf Professional Publishing, 2015)
'Nearly every gallon (or litre!) of fuel which is used in transport vehicles (cars, trucks, trains, aeroplanes etc.) is derived from oil which is extracted in the crude state from oil wells and which is then processed in an oil refinery to yield the required transport fuel (gasoline, diesel, kerosene etc). The first task in the refinery is to separate these useful fuels from the crude oil by the process of distillation in which the components of the oil are separated on the basis of their volatility. Of course, the components of crude oil which are of volatility too low to allow them to be used as fuels are also separated in the distillation process and can be either directly used (for example as lubricating or fuel oils) or can be chemically converted to more volatile materials'--
Machine generated contents note: Preface Introduction 1. Fouling in Crude Distillation Units : Basic Science and Economics
Includes bibliographical references : (pages 329-360) and index.
Keywords: Petroleum products -- Analysis; Petroleum -- Refining -- Simulation methods; Contamination (Technology) -- Measurement; Fouling -- Simulation methods; Heavy oil -- Simulation methods